Growth of GaN-based LED on C-plane GaN substrate / Sivanathan Pariasamy @ Chelladurai - Sivanathan , Pariasamy @ Chelladurai (2018)
The InGaN/GaN multi-quantum wells, growth on bulk GaN substrate were studied for blue light emission via metal-organic chemical vapor deposition (MOCVD). The homoepitaxy growth of GaN-on-GaN gives an unprecedented high performance with low defect density, high-quality crystal, simplified LED architectures (short process flow) and overall lower cost. The optimizations of InGaN/GaN MQWs on n-type GaN substrate for blue emission at 445-455 nm range were carried out. The high quality 6 pairs of multi-quantum wells with InGaN quantum wells and GaN quantum barriers were grown at different temperatures (650to 780). The lowest defect density demonstrated at 1.3107 cm